Răspuns :
ab=-2/5
ac=1/3
ab+ac=-2/5+1/3
a(b+c)=(-6+5)/15=-1/15
ab-ac=-2/5-1/3
a(b-c)=(-6-5)/15=-11/15
ac=1/3
ab+ac=-2/5+1/3
a(b+c)=(-6+5)/15=-1/15
ab-ac=-2/5-1/3
a(b-c)=(-6-5)/15=-11/15
ab=-2/5
5ab=-2
b=-2/5a
ac=1/3
3ac=1
c=1/3a
a)a(b+c)=a(-2/5a+1/3a)=a[(-6+5)/15a]=a·(-1/15a)=-1/15=-0,0(6)
b)a(b-c)=a((-2/5a-1/3a)=a[(-6-5)/15a]=a·(-11/15a)=-11/15=-0,7(3)
5ab=-2
b=-2/5a
ac=1/3
3ac=1
c=1/3a
a)a(b+c)=a(-2/5a+1/3a)=a[(-6+5)/15a]=a·(-1/15a)=-1/15=-0,0(6)
b)a(b-c)=a((-2/5a-1/3a)=a[(-6-5)/15a]=a·(-11/15a)=-11/15=-0,7(3)